The Institutional Educational Project from to Sport. A Theoretical Review (Revista horizonte, 2022)
This article reviews the existing literature referring to the construction of the institutional educational project from sports in school organizations. The main findings show that the mission and vision of an educational establishment can be oriented towards sportsmanship, as a sign of the educational value of school sports. Based on the collection of the information, an exhaustive bibliographic review was carried out in search engines of academic articles related to the research topic. The main conclusions indicate that the emancipatory role of school sports is fundamental in our society for the formation of democratic citizens with high ethical moral values and works as an excellent pedagogical tool and educational resource.